On-farm harvest timing effects on alfalfa weevil across the Intermountain West region of the United States - Herreid, Judith S.; Rand, Tatyana A.; Cockrell, Darren M.; Peairs, Frank B.; Jabbour, Randa (Frontiers in Insect Science, 2024)
Alfalfa (Medicago sativa L.) is an economically important commodity in the Intermountain Western United States. A major concern for alfalfa producers in this region is the alfalfa weevil (Hypera postica Gyllenhal). Insecticide resistance development coupled with regulatory changes in pesticide use has resulted in renewed interest by producers in non-chemical control methods such as cultural control. One such cultural control method is early harvest, which consists of producers timing their harvests early in the season to decrease alfalfa weevil damage. This method is thought to be effective by exposing weevil larvae to adverse conditions before significant damage occurs. Still, early harvest can be difficult to employ because recommendations are often vague. To better understand how early harvest impacts both alfalfa weevils and their natural enemies and how producers are using this method across the Intermountain Western United States, we conducted a study in alfalfa production fields in Colorado, Montana, and Wyoming over three growing seasons. We determined that the timing of the initial alfalfa harvest spanned more than one month across fields, and alfalfa plant stage at harvest ranged from late vegetative to early bloom. Harvest was more impactful on reducing alfalfa weevil densities the earlier it was implemented. Removing windrows in a timely manner is likely useful to further decrease alfalfa weevil densities. Harvest timing was not associated with parasitism rates of alfalfa weevil, but higher parasitism rates were associated with lower post-harvest alfalfa weevil densities. This work has increased our understanding of early harvest in an on-farm setting and to improve recommendations for producers across the Intermountain Western United States.